Pengaruh Terapi Metotreksat pada Pasien Artritis Reumatoid terhadap Penurunan Fungsi Kognitif: Meta-Analisis Berdasarkan Telaah Sistematik - Fauzia, Fara; Prihartono, Nurhayati Adnan; Hidayat, Rudy; Araminta, Abirianti P. (UI Scholars Hub, 2023)
Introduction. Rheumatoid arthritis (RA) is a systemic and chronic autoimmune disease involving the joints disorder as the main manifestations. Methotrexate (MTX) is currently still the drug of choice for RA treatment due to the good clinical response. However, there was a case reported by the American Geriatric Society in 2015 regarding the presence of reversible dementia after treatment with low-dose oral methotrexate. This study aimed to identify the effect of MTX treatment on cognitive disorder in RA patients. Methods. The study protocol was registered with PROSPERO (CRD42023414937). A systematic literature search was conducted in Medline Embase database, Scopus, CENTRAL to identify cohort observational studies, case controls, and randomized control trial (RCT) studies, evaluating the effect of methotrexate therapy on cognitive function disorder in RA patients. The Newcastle-Ottawa Scale (NOS Scale) was used to analyze the quality of existing observational studies and The COCHRANE was used to analyze the RCT studies which included in the journals reviewed. Results. There were 4 observational studies that met the criteria, including 2 case control studies and 2 cohort studies. Pooling was carried out in two different types of studies. The OR was 0.81 (95%CI 0.4 – 1.68) in the case control studies group, whereas the RR was 0.88 (95% CI 0 .6 – 1.3) in the cohort studies group. The heterogeneity of each type of case-control studies and cohort studies were I2 92% (p-value277% (p-value Conclusion. Methotrexate therapy has not been proven to have an effect on cognitive disorder in RA patients either as a protective factor or as a risk factor.